Tradisi Hadis Klasik dan Pembaruannya di Indonesia: Telaah Pemikiran Ali Mustafa Yaqub - Fitri Idani; Abd. Wahid (Al-Widad, 2023)
Ideally, hadith studies in Indonesia should integrate the strengths of classical methodology with a contextual approach relevant to contemporary developments. However, in reality, a dichotomy persists between a textualist understanding and an overly liberal approach without a strong methodological foundation. This situation creates epistemological problems in understanding hadith proportionally within society. Therefore, this study aims to analyze Ali Mustafa Yaqub's thoughts regarding hadith tradition and renewal in Indonesia, particularly in bridging the tension between classical and contextual approaches. This study is a qualitative literature study, employing descriptive-analytical methods. Data were obtained from Ali Mustafa Yaqub's works as primary sources, and supporting literature as secondary sources. Data analysis was conducted using content analysis techniques with an interpretative-critical approach to understand his thought patterns in depth. The results show that Ali Mustafa Yaqub offers a moderate approach by maintaining classical hadith methodology while opening up space for contextualization. His critique is corrective to excessive literalism and liberalism, while his renewal emphasizes the integration of text and context. This approach is relevant in addressing the challenges of contemporary, pluralistic and dynamic Indonesia.